A prospective cohort study to identify and evaluate endotypes of venous thromboembolism: Rationale and design of the Genotyping and Molecular Phenotyping in Venous ThromboEmbolism project (GMP-VTE). Issue 181 (September 2019) - Ten Cate, V.; Koeck, T.; Panova-Noeva, M.; Rapp, S.; Prochaska, J.H.; Lenz, M.; Schulz, A.; Eggebrecht, L.; Hermanns, M.I.; Heitmeier, S.; Krahn, T.; Laux, V.; et al.
Abstract: Several clinical, genetic and acquired risk factors for venous thromboembolism (VTE) have been identified. However, the molecular pathophysiology and mechanisms of disease progression remain poorly understood. This is reflected by uncertainties regarding the primary and secondary prevention of VTE and the optimal duration of antithrombotic therapy. A growing body of literature points to clinically relevant differences between VTE phenotypes (e.g. deep vein thrombosis (DVT) versus pulmonary embolism (PE), unprovoked versus provoked VTE). Extensive links to cardiovascular, inflammatory and immune-related morbidities are testament to the complexity of the disease. The GMP-VTE project is a prospective, multi-center cohort study on individuals with objectively confirmed VTE. Sequential data sampling was performed at the time of the acute event and during serial follow-up investigations. Various data levels (e.g. clinical, genetic, proteomic and platelet data) are available for multi-dimensional data analyses by means of advanced statistical, bioinformatic and machine learning methods. The GMP-VTE project comprises n = 663 individuals with acute VTE (mean age: 60.3 ± 15.9 years; female sex: 42.8%). In detail, 28.4% individuals ( n = 188) had acute isolated DVT, whereas 71.6% subjects ( n = 475) had PE with or without concomitant DVT. In the study sample, 28.9% ( n = 129) of individuals with PE and 30.1% ( n = 55) of individuals with isolated DVT had a recurrent VTE event at the time of study enrolment. The systems-oriented approach for the comprehensive dataset of the GMP-VTE project may generate new biological insights into the pathophysiology of VTE and refine our current understanding and management of VTE.